Ultra‐low radiation dose during electrophysiology procedures using optimized new generation fluoroscopy technology. Issue 8 (21st July 2017) - Crowhurst, James; Haqqani, Haris; Wright, Daniel; Whitby, Mark; Lee, Adam; Betts, John; Denman, Russell
Abstract: Background: Electrophysiology procedures require fluoroscopic guidance, with the associated potentially adverse effects of ionizing radiation. Newer fluoroscopy systems have more features that enable dose‐reduction strategies. This study aimed to investigate any reduction in radiation dose between an older fluoroscopy system (Philips Integris H5000, Philips Healthcare, Einhoven, Netherlands) and one of the latest systems (Siemens Artis Q, Siemens Healthcare, Erlangen, Germany), optimized with dose‐reduction strategies. Methods: Radiation dose measures were collected over a 2‐year period in a single electrophysiology laboratory. Procedures were separated into seven groups: devices, biventricular devices, electrophysiology studies, standard radiofrequency ablation, complex atrial ablation, ablation for ventricular arrhythmias, and pulmonary vein isolation. In the first year, an older fluoroscopy system was used, and in the second year, a new system, with dose reduction strategies. Comparisons were also made to the literature with regard to radiation dose levels. Results: Patient characteristics, fluoroscopy times, number of digital acquisitions, procedural times, and procedural success were largely similar between the old and new system across procedure groups. Overall dose area product (DAP) was reduced by 91% (5.0 [2.0–17.0] to 0.45 [0.16–2.61] Gycm 2 [P > 0.001]) with the new system and was lower across all groups. DAP readings with the new system are some of the lowest published in the literature in all groups. Conclusion: An optimized contemporary digital fluoroscopy system, with low radiation dose configuration and continued good procedural practice, can result in ultra‐low radiation levels for all electrophysiology procedures, without compromising procedural time or procedural success.